2007
DOI: 10.1016/j.crvi.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype, gelling agent, and auxin on the induction of somatic embryogenesis in sweet potato (Ipomoea batatas Lam.)

Abstract: Lateral buds of six cultivars of sweet potato were induced to form embryogenic callus in a culture medium solidified with two types of gelling agents, Agar or Gelrite, and supplemented with various concentrations of auxins, 2,4-D, 2,4,5-T and Picloram. Of the six cultivars screened, only three gave an embryogenic response. Best results with an average of 3.53% embryogenic response were obtained with the medium solidified with Agar, while in Gelrite only 0.45% of lateral buds gave rise to embryogenic callus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Factors such as the effects of PGRs, reduced nitrogen, plant species and genotype of the cultured material have an effect on the induction and proliferation of embryos (El Abidine Triqui et al 2008). Even radiation can play a key role in somatic embryogenesis (Begum et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Factors such as the effects of PGRs, reduced nitrogen, plant species and genotype of the cultured material have an effect on the induction and proliferation of embryos (El Abidine Triqui et al 2008). Even radiation can play a key role in somatic embryogenesis (Begum et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These results were similar to those of Belarmino and Gonzales (2008) who revealed that picloram is essential for callus induction and somatic embryogenesis in yam. Picloram has been successfully employed for the induction of friable embryogenic calli in root and tuber crops, especially cassava, sweet potato, and yam (Nyaboga et al 2013;Triqui et al 2008;Belarmino and Gonzales 2008). The copper sulfate used in the media combination with auxins creates oxidative stress conditions that promote both cell division and embryogenic cell formation, as reported by Pasternak et al (2002).…”
Section: Effect Of Different Concentrations Of Picloram Supplemented mentioning
confidence: 99%
“…Its stems and foliage are also used as forage. 27 Sweet potato is also rich in vitamin A, B, and C, iron, phosphorous, and calcium. In recent years, several methods have been employed in the improvement of sweet potato crop but breeding is constrained by the complexity of the genetics of this out-crossing hexaploid crop (2n = 6x = 96) and lack of genomic resources.…”
Section: Introductionmentioning
confidence: 99%